2015
DOI: 10.1126/science.aab1852
|View full text |Cite
|
Sign up to set email alerts
|

Morphinan biosynthesis in opium poppy requires a P450-oxidoreductase fusion protein

Abstract: Morphinan alkaloids from the opium poppy are used for pain relief. The direction of metabolites to morphinan biosynthesis requires isomerization of (S)- to (R)-reticuline. Characterization of high-reticuline poppy mutants revealed a genetic locus, designated STORR [(S)- to (R)-reticuline] that encodes both cytochrome P450 and oxidoreductase modules, the latter belonging to the aldo-keto reductase family. Metabolite analysis of mutant alleles and heterologous expression demonstrate that the P450 module is respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 36 publications
1
90
0
3
Order By: Relevance
“…Recently, fusion between a cytochrome P450 (CYP) monooxygenase and an NADPH-dependent aldo-keto reductase (AKR) was shown to catalyze the S to R stereochemical inversion of reticuline as the gateway reaction to morphinan alkaloid biosynthesis in opium poppy3435. The CYP-AKR fusion was also detected in Persian poppy ( Papaver bracteatum ), which accumulates the morphinan alkaloid thebaine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fusion between a cytochrome P450 (CYP) monooxygenase and an NADPH-dependent aldo-keto reductase (AKR) was shown to catalyze the S to R stereochemical inversion of reticuline as the gateway reaction to morphinan alkaloid biosynthesis in opium poppy3435. The CYP-AKR fusion was also detected in Persian poppy ( Papaver bracteatum ), which accumulates the morphinan alkaloid thebaine.…”
Section: Discussionmentioning
confidence: 99%
“…One important step was missing until June 2015, when the conversion of (S)-reticuline to (R)-reticuline via 1,2-dehydroreticuline was elucidated [9 ]. The (S)-reticuline to (R)-reticuline conversion opens the way from the general BIA pathway to the morphinans and is catalyzed by a unique fusion protein composed of a cytochrome P450 monooxygenase (CYP) and an oxidoreductase of the aldo-keto-reductase type named STORR ('S to R' reticuline).…”
Section: Biosynthetic Steps: Enzymes and Genesmentioning
confidence: 99%
“…However, functionally expressing the more than 20 heterologous genes required for complete biosynthesis of these complex molecules has been challenging because of the decreases in titer observed with each additional enzymatic step. Also, key enzyme(s) that epimerize the ( S )-benzylisoquinoline scaffold to the ( R )-enantiomer, which is the biosynthetic precursor of the promorphinan and morphinan scaffolds, have remained unknown even after decades of study until recently identified by two groups (19, 20) and by our team as described below…”
mentioning
confidence: 99%
“…2A), the 1,2-dehydroreticuline synthase (DRS) and 1,2-dehydroreticuline reductase (DRR) enzyme(s) had not been isolated and sequenced when we began our study (2729). While we were preparing this manuscript for submission, one group reported the discovery of this enzyme in P. somniferum by characterizing mutant alleles from chemically mutagenized opium poppy plants (19). While our manuscript was under review, another group reported using plant transcriptome databases to identify candidates and then cloned the gene from P. somniferum cDNA (20).…”
mentioning
confidence: 99%